Sodium-ion battery non-aqueous electrolyte and sodium-ion battery

By adding isobenzofurandicarbonitrile anhydride compounds to the non-aqueous electrolyte of sodium ion battery, the problem of poor circulation performance of sodium ion battery at high temperatures is solved, and a stable interface film and CEI film are formed, which significantly improves the high-temperature circulation and storage performance of the battery.

CN119695280APending Publication Date: 2025-03-25安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893321.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Sodium ion batteries have poor circulation performance at high temperatures, and the metal Fe ions dissolution and interfacial side reactions of sodium ferric sulfate materials have increased, resulting in thickening of CEI film and gas production. NaPF6 is unstable and easily produces HF and corrodes the interface.

Method used

Isobenzofurandicarbonitrile acid anhydride compound is added to the non-aqueous electrolyte of sodium ion battery. The anhydride functional groups of the compound can form a stable interface film, inhibit cracks and irreversible phase change, and the carbon-carbon double bond can polymerize on the surface of the positive electrode to form a thin and high-temperature stable CEI film.

Benefits of technology

It effectively inhibits the dissolution of metal Fe ions of sodium iron sulfate material at high temperatures, stabilizes the interface structure, reduces interface side reactions, and improves the high-temperature circulation and storage performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695280A_ABST
    Figure CN119695280A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion batteries, and relates to a sodium-ion battery electrolyte, in particular to a sodium-ion battery non-aqueous electrolyte and a sodium-ion battery. Comprising a sodium salt, a non-aqueous organic solvent and an additive, the additive comprises an isobenzofurandicarbonitrile anhydride compound, and the chemical structure of the isobenzofurandicarbonitrile anhydride compound is # imgabs0 #. By adding the isobenzofurandicarbonitrile anhydride compound into the electrolyte, the problem of high-temperature circulation of the sodium ion battery is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries and relates to a sodium ion battery electrolyte, and in particular to a sodium ion battery non-aqueous electrolyte and a sodium ion battery. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As a green and environmentally friendly energy storage device, lithium-ion batteries have been widely used in the fields of electronic consumption, energy storage and electric vehicles due to their advantages such as high energy density, long cycle life and low pollution. However, the content of lithium in the earth's crust is only 17ppm, and its reserves are extremely low and unevenly distributed, resulting in a continuous surge in the price of lithium-ion batteries, which can no longer meet the application needs of the above-mentioned fields.

[0004] Compared with lithium, sodium is abundant in reserves, widely distributed, and has a simple extraction process. Sodium-ion batteries and lithium-ion batteries have similar working principles and battery components; therefore, sodium-ion batteries have received more and more attention. Sodium iron sulfate is a positive electrode material because of its low cost, high rate performance, and stable cycle performance. However, sodium iron sulfate also has many defects: (1) Poor conductivity. Carbon materials are usually added during the preparation stage to solve the problem of poor conductivity. (2) The material has a large specific surface area and a small particle size, resulting in more side reactions at the interface. (3) Due to the large specific surface area, the material has strong water absorption and it is difficult to remove water. Especially at high temperatures, the side reactions at the interface increase, resulting in thickening of the CEI film and gas production at the interface. At the same time, at high temperatures, NaPF 6 Instability easily produces HF, which has a strong corrosive effect on the CEI film at the interface, further exacerbating the easy dissolution of metal ions on the positive electrode side. Therefore, in order to meet the requirements of high pressure and high temperature, it is imperative to carefully construct a stable CEI, and it is urgent to solve the problem of high temperature cycle of sodium ion batteries. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a sodium ion battery non-aqueous electrolyte and a sodium ion battery. The present invention solves the problem of high temperature cycle of sodium ion batteries by adding isobenzofuran dicarbonitrile anhydride compounds to the electrolyte.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] In a first aspect, a sodium ion battery non-aqueous electrolyte comprises a sodium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises an isobenzofuran dicarbonitrile anhydride compound, and the chemical structure of the isobenzofuran dicarbonitrile anhydride compound is as follows:

[0008] Its CAS number is: 64760-93-6.

[0009] The present invention adds an isobenzofuran dicarbonitrile anhydride compound to a non-aqueous electrolyte of a sodium ion battery. Firstly, the anhydride functional groups in the molecular structure of the compound are all electron-withdrawing groups, which are easily oxidized to form a CEI film, can form a uniform and stable interface film on the surface of a positive electrode, can effectively inhibit the generation of cracks, and inhibit irreversible phase change; secondly, the molecular structure of the compound contains a carbon-carbon double bond, can undergo a polymerization reaction on the surface of the positive electrode, so that the electrolyte additive can undergo an oxidative polymerization reaction and a decomposition reaction before a solvent, and a thinner CEI film is formed on the surface of the positive electrode. The formed CEI film has strong high-temperature stability, is not easy to break, and has certain Na ion conductivity.

[0010] In some embodiments, the sodium salt is sodium hexafluorophosphate (NaPF 6 ), sodium bis(fluorosulfonyl)imide (NaFSI), sodium perchlorate (NaClO 4 ) at least one of the following. When the sodium salt is selected as NaPF 6 and / or NaFSI, the obtained sodium ion battery non-aqueous electrolyte has better performance.

[0011] In some embodiments, the mass of the sodium salt is 10% to 25% of the total mass of the sodium ion battery non-aqueous electrolyte. When the mass of the sodium salt is 12% to 16% of the total mass of the sodium ion battery non-aqueous electrolyte, the performance of the obtained sodium ion battery non-aqueous electrolyte is better.

[0012] In some embodiments, the non-aqueous organic solvent is selected from one or more of organic esters, ethers, and sulfone solvents; preferably, it is a mixture of two or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dimethyl sulfoxide, cyclopentane sulfone and dimethyl sulfone.

[0013] In some embodiments, the mass of the non-aqueous organic solvent is 70% to 88%, preferably 72% to 85%, of the total mass of the non-aqueous electrolyte for the sodium ion battery.

[0014] In some embodiments, the mass of the isobenzofuran dicarbonitrile anhydride compound is 0.1% to 5% of the total mass of the sodium ion battery non-aqueous electrolyte, preferably 0.2% to 2%, and more preferably 0.5% to 1.8%.

[0015] In some embodiments, the additives further include other additives, and the other additives are selected from one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3-propylene sultone, methylene disulfonate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, tripropyl borate, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, sodium difluorophosphate, sodium bis(oxalatoborate) or sodium difluorooxalatoborate. Specifically, the mass of the other additives is 0.1% to 5% of the total mass of the sodium ion battery non-aqueous electrolyte.

[0016] On the other hand, a sodium ion battery comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the electrolyte is the non-aqueous electrolyte for sodium ion batteries described in the first aspect of the present invention.

[0017] The beneficial effects of the present invention are:

[0018] 1. The present invention adds an isobenzofuran dicarbonitrile anhydride compound to the non-aqueous electrolyte of a sodium ion battery, which can form a complex with a transition metal ion. The compound contains a carbon-carbon double bond and can undergo a polymerization reaction on the surface of the positive and negative electrodes. At the same time, the π electrons in the double bond can couple with the d orbital electrons in the transition metal element, thereby improving the interface stability of the positive electrode; the compound also contains anhydride groups that can form a uniform and stable interface film on the surface of the positive electrode, which can effectively inhibit the generation of cracks and inhibit irreversible phase changes; therefore, the sodium ion battery electrolyte provided by the present invention can inhibit the dissolution of metal Fe ions of the sodium iron sulfate material at high temperature, stabilize the interface structure, and inhibit interface side reactions, thereby improving the high-temperature cycle performance and high-temperature storage performance of the battery.

[0019] 2. The present invention adds isobenzofuran dicarbonitrile anhydride compounds to the non-aqueous electrolyte of sodium ion batteries, wherein the anhydride group can absorb trace amounts of water in the electrolyte, thereby reducing the damage of NaPF to the electrolyte caused by water. 6 The decomposition of HF can avoid the production of HF, thereby reducing the corrosion of HF on the interface of the positive electrode material, and further improving the high-temperature cycle performance and high-temperature storage performance of the battery.

[0020] 3. Experiments show that isobenzofuran dicarbonitrile anhydride compounds have the highest HOMO energy (-7.17eV) and the lowest LUMO energy (-1.05eV) in the non-aqueous electrolyte of sodium ion batteries. Therefore, they are more easily oxidized and reduced on the surfaces of the positive and negative electrodes to form a stable CEI film, which can further allow metal ions to overflow and improve the interface stability of the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 Schematic diagram of the mechanism of action of adding compound 1 on the interface of sodium iron sulfate (NFS) in an example of the present invention. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0024] Example 1

[0025] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0026] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), propylene carbonate (PC), ethylene carbonate (EC) and dimethyl carbonate (EMC) were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then sodium hexafluorophosphate (NaPF 6 ), stirring to completely dissolve; then adding compound 1, fluoroethylene carbonate (FEC) and sodium difluorooxalatoborate (NaODFB), mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 84.5:13.5:0.5:1:0.5.

[0027] Example 2

[0028] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0029] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 84.2:13.5:0.8:1:0.5.

[0030] Example 3

[0031] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0032] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 83.8:13.5:1.2:1:0.5.

[0033] Example 4

[0034] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0035] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 83.4:13.5:1.6:1:0.5.

[0036] Example 5

[0037] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0038] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 83:13.5:2:1:0.5.

[0039] Example 6

[0040] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0041] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are in a mass ratio of 84.8:13.5:0.2:1:0.5.

[0042] Example 7

[0043] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0044] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding compound 1, FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 , compound 1, FEC and NaODFB are 82.5:13.5:2.5:1:0.5.

[0045] Comparative Example 1

[0046] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0047] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding FEC and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 The mass ratio of FEC and NaODFB is 85:13.5:1:0.5.

[0048] Comparative Example 2

[0049] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0050] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent.6 , stirring to completely dissolve; then adding vinylene carbonate (VC) and NaODFB, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 The mass ratio of VC and NaODFB is 84.5:13.5:1.5:0.5.

[0051] Comparative Example 3

[0052] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0053] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding VC, NaODFB and succinic anhydride (SA), mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 The mass ratio of VC, NaODFB and SA is 84.5:13.5:0.5:0.5:1.

[0054] Comparative Example 4

[0055] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0056] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding VC, NaODFB and succinonitrile (SN), mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6 The mass ratio of VC, NaODFB and SN is 84.5:13.5:0.5:0.5:1.

[0057] Comparative Example 5

[0058] A sodium ion battery non-aqueous electrolyte, the preparation process of which is as follows:

[0059] In a glove box filled with argon (water <10 ppm, oxygen <10 ppm), PC, EC and EMC were mixed at a mass ratio of 2.5:0.5:7 to obtain a mixed solvent, and then NaPF was slowly added to the mixed solvent. 6 , stirring to completely dissolve; then adding VC, NaODFB, SA and SN, mixing evenly to obtain a sodium ion battery non-aqueous electrolyte, wherein the mixed solvent, NaPF 6The mass ratio of VC, NaODFB and SN is 82.5:13.5:1.5:0.5:1:1.

[0060] The electrolyte formulas of various embodiments and comparative examples are shown in Table 1.

[0061] Table 1 Electrolyte formula

[0062]

[0063]

[0064] Wherein, the chemical structural formula of compound 1 is: CAS number: 64760-93-6, purchased from Shenzhen Aituo Chemical Co., Ltd.

[0065] The sodium ion battery is prepared by using the electrolyte of each embodiment and comparative example, which specifically includes the following steps:

[0066] Preparation of positive electrode sheets: The positive electrode materials sodium iron sulfate, conductive carbon black Super-P, carbon nanotubes and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 96.5:2:0.3:1.2, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain positive electrode slurry, and then the slurry is evenly coated on both sides of the aluminum foil, and the positive electrode sheets are obtained after drying and rolling.

[0067] Preparation of negative electrode sheet: Hard carbon, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) are mixed evenly in a mass ratio of 95:2:2:1, and then dispersed in deionized water to obtain negative electrode slurry. The slurry is then evenly coated on both sides of the aluminum foil, and the negative electrode sheet is obtained after drying and rolling.

[0068] Preparation of sodium iron sulfate battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, ensure that the separator separates the positive electrode sheet and the negative electrode sheet, and the negative electrode sheet completely covers the positive electrode sheet, and then put the stacked battery cell into an aluminum-plastic film packaging bag, and then inject the above-prepared electrolyte into the battery cell for formation, sealing, aging, secondary sealing, capacity division and other processes to make a sodium iron sulfate battery with a capacity of 1000mAh.

[0069] The specific test conditions are as follows:

[0070] (1) High-temperature electrolyte acidity test: Prepare the electrolyte in a glove box filled with argon, put it into an aluminum-plastic bottle, place it in a 55°C oven for 48 hours, and then measure the change in the electrolyte acidity;

[0071] (2) High temperature cycle test: At high temperature (45°C), the sodium ion battery is charged and discharged at 1C / 1C (the battery discharge capacity is C 0 ), the upper limit voltage is 4.3V, the lower limit voltage is 2.8V, and then 1C / 1C charging and discharging is performed at room temperature for 800 cycles (the battery discharge capacity is C 1 );

[0072] Capacity retention rate = (C 1 / C 0 )*100%;

[0073] (3) Metal ion test of negative electrode sheet after cycling: The cycled battery is disassembled in a drying room, the negative electrode sheets are collected, the negative electrode sheets are rinsed with DMC several times and then dried, and the negative electrode powder is scraped for ICP testing.

[0074] The test data of the embodiments and comparative examples are shown in Table 2.

[0075] Table 2 Test data

[0076]

[0077] The results show that:

[0078] Comparative Example 1 is the basic formula group. From the analysis of the electrolyte acidity test data after high-temperature storage: compared with Comparative Example 1, the acidity of the electrolyte after high-temperature storage in Examples 1 to 7 is significantly lower than that in Comparative Example 1. This is because the anhydride functional group can absorb possible water molecules and neutralize the HF produced by the decomposition of sodium hexafluorophosphate after the addition of compound 1. This also explains why the acidity in the examples is less than that in the control group. Compared with Examples 1 to 5, the acidity value of Example 6 is significantly higher, which may be due to the low content of compound 1.

[0079] It can also be seen from the analysis of the high temperature cycle results that the high temperature cycle performance of Examples 1 to 5 is significantly better than that of Comparative Examples 1 to 4. This is because the addition of Compound 1 inhibits the increase in electrolyte acidity. At the same time, the HOMO and LUMO energies of EC, DEC and Compound 1 are calculated using first principles, showing that Compound 1 has the highest HOMO energy (-7.17 eV) and the lowest LUMO energy (-1.05 eV). Therefore, Compound 1 is more easily oxidized and reduced on the positive and negative electrode surfaces than EC and DEC. The mechanism is as follows: Figure 1As shown, the anhydride functional groups in the molecular structure are all electron-withdrawing groups, which are easily oxidized to form a CEI film, and can form a uniform and stable interface film on the positive electrode surface, which can effectively inhibit the generation of cracks and irreversible phase changes; at the same time, the additives containing carbon-carbon double bonds in the molecular structure can undergo polymerization reaction on the positive electrode surface. The electrolyte additive will undergo oxidative polymerization reaction and decomposition reaction before the solvent, forming a thinner CEI film on the positive electrode surface. The CEI film formed has strong high-temperature stability, is not easy to break, and has a certain Na ion conductivity.

[0080] ICP test was performed on the negative electrode after cycling: compared with Examples 1 to 5 and 7 and Comparative Examples 1 to 3 and 5, a significant reduction in Fe ions was observed. This was not only due to the stable CEI film, but also because the cyanide bond of the cyanide functional group could couple with the d-orbital electrons in the transition metal element at the interface to form a stable complex, inhibiting the dissolution of metal ions and thus improving the interface stability of the positive electrode.

[0081] Compared with Examples 1 to 5, the acidity of Comparative Example 5 does not change much, and the metal ion dissolution is not much different, but the high temperature cycle is worse. The additive in Comparative Example 5 and the additive compound 1 in the examples have the same effect in controlling acidity and metal ion dissolution. The reason for the high temperature difference may be that the polymer film of VC has poorer high temperature performance than compound 1, and the polymer CEI film formed by this compound 1 can be firmly combined with transition metal ions, making the CEI film more stable. In Example 7, 2.5% of compound 1 was added, but the high temperature cycle performance deteriorated. The possible reason is that the formed CEI is too thick, resulting in poor Na ion conductivity.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte for a sodium ion battery, comprising a sodium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises an isobenzofuran dicarbonitrile anhydride compound, and the chemical structure of the isobenzofuran dicarbonitrile anhydride compound is as follows:

2. The sodium ion battery nonaqueous electrolyte according to claim 1, characterized in that: The sodium salt is at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide and sodium perchlorate, preferably sodium hexafluorophosphate and / or sodium bis(fluorosulfonyl)imide.

3. The sodium ion battery nonaqueous electrolyte according to claim 1, characterized in that: The mass of the sodium salt is 10% to 25% of the total mass of the sodium ion battery non-aqueous electrolyte. When the mass of the sodium salt is 12% to 16% of the total mass of the sodium ion battery non-aqueous electrolyte, the performance of the obtained sodium ion battery non-aqueous electrolyte is better.

4. The sodium ion battery nonaqueous electrolyte according to claim 1, characterized in that: The non-aqueous organic solvent is selected from one or more of organic ester solvents, ether solvents, and sulfone solvents.

5. The sodium ion battery non-aqueous electrolyte according to claim 1, characterized in that: The non-aqueous organic solvent is selected from two or more of the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dimethyl sulfoxide, cyclopentane and dimethyl sulfone.

6. The sodium ion battery nonaqueous electrolyte according to claim 1, characterized in that: The mass of the non-aqueous organic solvent is 70% to 88%, preferably 72% to 85%, of the total mass of the non-aqueous electrolyte for the sodium ion battery.

7. The sodium ion battery nonaqueous electrolyte according to claim 1, wherein The mass of the benzofuran dicarbonitrile anhydride compound is 0.1% to 5% of the total mass of the sodium ion battery non-aqueous electrolyte, preferably 0.2% to 2%, and more preferably 0.5% to 1.8%.

8. The non-aqueous electrolyte for sodium ion batteries according to claim 1, wherein: The additives also include other additives, and the other additives are selected from one or more of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, 1,3-propane sultone, 1,3-propylene sultone, methylene disulfonate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, tripropyl borate, 1,3,6-hexanetrinitrile, 1,2-bis(cyanoethoxy)ethane, sodium difluorophosphate, sodium bis(oxalatoborate) or sodium difluorooxalatoborate.

9. The non-aqueous electrolyte for sodium ion batteries according to claim 8, characterized in that: The mass of the other additives is 0.1% to 5% of the total mass of the sodium ion battery non-aqueous electrolyte.

10. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The electrolyte is the non-aqueous electrolyte for sodium ion batteries according to any one of claims 1 to 8.